One-time phosphate fertilizer application to grassland columns modifies the soil microbiota and limits its role in ecosystem services - Ikoyi, I; Fowler, A; Schmalenberger, A (Elsevier, 2018)
This study evaluated the effect of one-time phosphate fertilization on the soil microbiota, its cycling of phosphorus (P) and grass growth. Soil columns were established in a greenhouse using a P-limited Irish soil (index 1), planted with Lolium perenne and fertilized with 0 (control), 5 (quarter), 10 (half) and 20 (full) kg P ha−1 as inorganic phosphate. Only traces of phosphate in soil solution were detected over the 14 week experiment, even after phosphate fertilization. Grass dry matter yield between treatments was not significantly different. Full phosphate fertilization significantly reduced the arbuscular mycorrhization (AM) rate, bacterial- and fungal-feeding nematode population, bacterial phoD gene abundance, but increased alkaline and acid phosphatase activities at the time of harvest. Full and half P treatments significantly shifted the bacterial, fungal and AM community structures compared to the control. Furthermore, the control had a significantly higher relative abundance of bacterial genera including Bacillus, Bradyrhizobium, Paenibacillus, Nocardioides and Balneimonas, that have been associated with P mobilization in the past, when compared to the full phosphate treatment. These results suggest that a positive effect of a single phosphate application on plant growth in a soil can be cancelled out by its negative effect on the soil microbiota and their ecosystem services.